Molecular Factors of Cell Antiviral Immunity - Selinger, Martin (Jihočeská univerzita, 2020)
The proposed thesis focuses on the description of flavivirus-host interactions in case of tick-borne encephalitis virus (TBEV) and Zika virus (ZIKV). In more detail, the TBEV-induced host responses in human cells of neural origin and interferon-mediated protection were described together with the identification of a new phenomenon of TBEV-induced host transcriptional and translational shut-off. In addition, virus-derived molecules with hypothetical immunomodulatory characteristics, TuORF and ZIKV sfRNA, were analysed for their presence and possible function during the infection.
Molecular Factors of Cell Antiviral Immunity
Keywords: flaviviruses; tick-borne encephalitis virus; Zika virus; host response; neural cells; interferon; flaviviruses; tick-borne encephalitis virus; Zika virus; host response; neural cells; interferon